Paper on the identification of the flexicurity profile of Member States using micro-economic data - Ronald Bachmann; Peggy Bechara; Sandra Schaffner (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
[Introduction:] The performance of the labour market has been one of the primary interests of policymakers in many countries around the world, and the importance of this issue has been further enhanced by the current financial and economic crisis. In this context, a well-functioning labour market has to strike a balance between two principles. On the one hand, a sufficient level of flexibility of the labour market makes it possible for employers to adjust their firms' labour force in order to react to changes in product demand and technological progress; employees may also benefit from flexibility if overall productivity and labour demand is increased. Furthermore, labour market flexibility may reduce or even prevent a segregation of the labour market if barriers to labour market entry are lowered. On the other hand, a certain level of security is important for the well-being of workers, and it may also be beneficial for employers as it reduces uncertainty and hence facilitates investment and production decisions. The combination of these two principles has lead to the term "flexicurity". (...)
Additional information: Final Report – October 2011. Research Project for the European Commission
Keywords: 330